2020
DOI: 10.1080/13880209.2020.1831026
|View full text |Cite
|
Sign up to set email alerts
|

Preventive treatment with ginsenoside Rb1 ameliorates monocrotaline-induced pulmonary arterial hypertension in rats and involves store-operated calcium entry inhibition

Abstract: (2020) Preventive treatment with ginsenoside Rb1 ameliorates monocrotaline-induced pulmonary arterial hypertension in rats and involves store-operated calcium entry inhibition,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Most of the seven compounds identified in our chemical analysis have been shown to have anti-hypertensive activities in various animal models, for example, Notoginsenoside R1 ( Yang et al, 2015 ), Ginsenoside RG1 ( Chen et al, 2012 ; Pan et al, 2012 ; Li et al, 2013 ), Ginsenoside Rb1 ( Wang et al, 2015 ; Jiang et al, 2017 ; Wang et al, 2020 ), Sodium Danshensu ( Tang et al, 2011 ; Zhang et al, 2016 ; Zhang et al, 2018 ; Liu H. et al, 2020 ), and Salvianolic acid B ( Fu et al, 2012 ; Xu et al, 2012 ; Zhao et al, 2012 ; Du et al, 2014 ; Ling et al, 2017 ). Interestingly, Ginsenoside RG1 has also been shown to have a protective effect for organ damage in SHR ( Chen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…Most of the seven compounds identified in our chemical analysis have been shown to have anti-hypertensive activities in various animal models, for example, Notoginsenoside R1 ( Yang et al, 2015 ), Ginsenoside RG1 ( Chen et al, 2012 ; Pan et al, 2012 ; Li et al, 2013 ), Ginsenoside Rb1 ( Wang et al, 2015 ; Jiang et al, 2017 ; Wang et al, 2020 ), Sodium Danshensu ( Tang et al, 2011 ; Zhang et al, 2016 ; Zhang et al, 2018 ; Liu H. et al, 2020 ), and Salvianolic acid B ( Fu et al, 2012 ; Xu et al, 2012 ; Zhao et al, 2012 ; Du et al, 2014 ; Ling et al, 2017 ). Interestingly, Ginsenoside RG1 has also been shown to have a protective effect for organ damage in SHR ( Chen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 97%
“…Saponins are the most important active ingredients in P. notoginseng (Burkill) F. H. Chen flower [ 29 , 30 ]. In the present study, we detected that PNFS contained nine saponins, of which the more abundant ginsenoside Rb1, ginsenoside Rg1, ginsenoside Rb3 and ginsenoside Rd all clearly have certain anti-hypertensive effects [ 43 46 ], which may be the basis of the anti-hypertensive components of PNFS, while the most abundant ginsenoside Rc and ginsenoside Rb2 are currently reported to have mainly cardioprotective effects [ 47 , 48 ], and whether they have anti-hypertensive effects remains to be further investigated. Previous studies have shown that PNFS can lower blood pressure in SHR, reduce the levels of TC and LDL-c, and regulate lipids in rat hyperlipidemia models [ 36 , 37 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rb1, which is the main pharmacologically active component of Chinese herbs such as Ginseng and Panax notoginseng , can exert anti-vascular smooth muscle cell proliferation and anti-inflammatory effects by specifically binding to estrogen receptor-β [ 157 ]. Experiments in vitro and in vivo confirmed that ginsenoside Rb1 inhibited SOCE, and the improvement of pulmonary vascular remodeling and the inhibition of cell proliferation and migration were observed in the MCT-induced PH rat model and isolated PASMCs, respectively [ [158] , [159] , [160] ]. Simultaneously, ginsenoside Rb1 treatment significantly ameliorate pulmonary hemodynamic status and right ventricle (RV) hypertrophy, as illustrated by decreased values of mPAP (34.1 ± 4.5 vs. 53.6 ± 5.6 mmHg, MCT + Rb1 vs. MCT, P < 0.01), RVSP (47.3 ± 8.1 vs. 68.9 ± 9.0 mmHg, MCT + Rb1 vs. MCT, P < 0.01), and RVHI (0.380 ± 0.047 vs. 0.628 ± 0.077 mmHg, MCT + Rb1 vs. MCT, P < 0.01) compared with administration of MCT alone [ 160 ].…”
Section: Traditional Chinese Medicine Monomers Inhibiting the Prolife...mentioning
confidence: 99%
“…Experiments in vitro and in vivo confirmed that ginsenoside Rb1 inhibited SOCE, and the improvement of pulmonary vascular remodeling and the inhibition of cell proliferation and migration were observed in the MCT-induced PH rat model and isolated PASMCs, respectively [ [158] , [159] , [160] ]. Simultaneously, ginsenoside Rb1 treatment significantly ameliorate pulmonary hemodynamic status and right ventricle (RV) hypertrophy, as illustrated by decreased values of mPAP (34.1 ± 4.5 vs. 53.6 ± 5.6 mmHg, MCT + Rb1 vs. MCT, P < 0.01), RVSP (47.3 ± 8.1 vs. 68.9 ± 9.0 mmHg, MCT + Rb1 vs. MCT, P < 0.01), and RVHI (0.380 ± 0.047 vs. 0.628 ± 0.077 mmHg, MCT + Rb1 vs. MCT, P < 0.01) compared with administration of MCT alone [ 160 ]. Lin et al [ 161 ] found that hypoxia stimulated the proliferation of rat PASMCs and up-regulated the expression of serotonin transporter (SERT) and 5-HT 1B receptor (5-HT1BR); nevertheless, ginsenoside Rb1 significantly inhibited this effect in a concentration-dependent manner, which may be related to the inhibition of Rho/Rho-kinase pathway.…”
Section: Traditional Chinese Medicine Monomers Inhibiting the Prolife...mentioning
confidence: 99%